Vliv ultrastruktury spermií na výsledek fertilizace in vitro - Žáková, Jana; Sedláčková, M; Ventruba, Pavel; Trávník, Pavel (Česká gynekologie, 1997)
The ultrastructure of sperm cells in cumulus oophorus of the human oocyte 20 hrs after in vitro fertilization (WF) was studied. Materials and methods: Mechanically removed cumular cells were processed for electron microscopy and the spermatozoa deposited in the intracellular spaces as well as those penetrating into follicular cells were evaluated. The samples were divided into three groups. Group I contained cumuli from unfertilized oocytes, group II involved those from fertilized oocytes, hut not pregnancy after embryo transfer. Group III was formed by cumuli from fertilized oocytes of patients, where pregnancy had been achieved. Results: In group I numerous anomalies of spermatozoal ultrastructure were found, such as head malformations, incompleted chromatin condensation, large cytoplasmatic droplets, etc. In groups II and III, about 70 % normal sperm cells were found. Conclusions: These findings provide evidence of the important role of the morphological quality of spermatozoa in the failure of in vitro fertilization, also in cases where anomalies could not be detected by the usual methods of sperm examination.
Keywords: Fertilization in Vitro; techniky in vitro; Spermatozoa; spermie; fertilizace in vitro; In Vitro Techniques